1994
DOI: 10.1128/aac.38.12.2908
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of 2,2'-bipyridyl analogs against Mycobacterium leprae

Abstract: In vitro susceptibility ofMycobacterium leprae to two bipyridyl analogs was studied by using two biochemical parameters to measure the metabolic activity of the organism. VUF-8514 at 0.16 ,uglml, but not VUF-8842, completely inhibited the metabolic activity of M. keprae, and the action was bactericidal. When compared to rifampin (MIC 0.3 ,ug/ml), VUF-8514 was equally bactericidal against M. keprae. The aim of the present study was to evaluate the activities of these analogs, in comparison to that of rifampin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…When tested in axenic culture medium, this compound was reported to inhibit the growth of several microorganisms such as Mycoplasma spp. (12), Candida albicans (41), and Escherichia coli (41), as well as mycobacterial species including Mycobacterium tuberculosis (13), Mycobacterium avium (13), and Mycobacterium leprae (14). However, further studies on the pharmacology and toxicology of VUF 8514 will be required to determine its potential usefulness in the treatment of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…When tested in axenic culture medium, this compound was reported to inhibit the growth of several microorganisms such as Mycoplasma spp. (12), Candida albicans (41), and Escherichia coli (41), as well as mycobacterial species including Mycobacterium tuberculosis (13), Mycobacterium avium (13), and Mycobacterium leprae (14). However, further studies on the pharmacology and toxicology of VUF 8514 will be required to determine its potential usefulness in the treatment of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A diaminopyrimidine with attractive properties for the treatment of Gram-positive infections or infections by several opportunistic proto- zoa, 106,107 epiroprim is one of the most active DHFR inhibitors against Mycobacterium ulcerans and exerted synergism when combined with dapsone. 108 Epiroprim is also synergistic with dapsone against Mycobacterium leprae in vivo. 109 To the best of our knowledge, there is no development work ongoing with this compound.…”
Section: New Drugs and Drugs In Developmentmentioning
confidence: 99%
“…108 Epiroprim is also synergistic with dapsone against Mycobacterium leprae in vivo. 109 To the best of our knowledge, there is no development work ongoing with this compound. Pyrimethamine/Dapsone (Maloprim).…”
Section: New Drugs and Drugs In Developmentmentioning
confidence: 99%
“…In vitro experiments using THP‐1 macrophage cell lines and human peripheral monocyte‐derived macrophages infected with M. tuberculosis have shown that the minimum bactericidal concentration of thioridazine is as low as 0.1 mg l −1 , with complete killing occurring within 3 days of infection [29]. Phenothiazines affect a number of key mycobacterial targets [31–33]. They bind to and inactivate calmodulin, a calcium transport protein which is a vital constituent of the cell wall envelope of mycobacteria [34–36].…”
Section: Antimicrobial Activity Of Thioridazinementioning
confidence: 99%